(3GdYbO GdefXhe aj PcQ CaGVd GdQhes - (3Ydj Hf dGdj HGdj GdQhej GdMfaj GdeYQha Hefbs; (3WGTcHQj RGOI , YUGe GdOjf CHh GdNjQ CMeO Hf eUWaj Hf Ndjd, WGTcHQj RGOg,J (B968 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg(B: (3hVGY CQHGH GdCdHGH cGdPHGH ai GdVHGH, aUGQ GdeYGQa Wja NjGd, Ch VjakG Ydi TQa GQJMGd s
(3BNQgG (B:s
(3ebHhdG Yf GdNGUI hGdYGeI GfJbd SfI CQHY hSJjf hJSYeGFI s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B257s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B427 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B635 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B289 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs